(untitled) (The Educator Journal, 2025)
This qualitative study explores basic level teachers’ perceptions and experiences of classroom assessment within Nepal’s integrated curriculum for Grades 1 to 3. Using a phenomenological design, the research investigates how teachers interpret, implement, and respond to assessment practices in the context of policy expectations and classroom realities. Data collected through semi-structured interviews and document analysis revealed five major themes: insufficient institutional support and training, community resistance to continuous assessment, inconsistencies between early and upper-grade assessments, administrative workload, and varied perceptions based on teaching context. Despite the curriculum’s constructivist foundation and alignment with assessment for learning (AfL) principles, findings indicate that teachers often lack the training, resources, and systemic support necessary to implement formative assessment effectively. The study concludes that to bridge the gap between policy and practice, greater emphasis must be placed on context-sensitive training, simplified assessment tools, and inclusive policy reform that acknowledges the lived experiences of teachers. These insights contribute to the growing discourse on sustainable implementation of integrated assessment models in developing education systems.